METABOLIC EFFECTS OF ALCOHOLISM AND ITS RELATIONSHIP WITH ALCOHOLIC LIVER DISEASE - Tabassum, Fauzia; Khurshid, Rukhshan; Karim, Samina; Akhtar, Mohd Saleem (Journal of Ayub Medical College Abbottabad, 2001)
Background. Chronic and excessive ethanol consumption is associated with cellular proliferation, fibrosis, cirrhosis and cancer of liver. It was planned to study the effect of alcohol on different biochemical parameters as distribution of these parameters may lead to several complications in gastrointestinal tract, liver, kidney, brain etc. Methods: 50 alcoholic males and 20 normal subject (with no history of alcohol) with an age ranges 30-45 years were included in the study. Biochemical parameters related to liver were estimated.by standard kit. Besides, ions and electrolytes were also determined by standard kit and flame photometer). Results: It was observed that level of alkaline phosphatase, alanine transferase, protein and globulin were significantly increased as compared to normal subjects. Besides, ions like calcium and phosphate were significantly decreased. On the other hand, the level of potassium and magnesium was significantly decreased as compared to normal subjects. Electrophoresis shows a protein of 100 Kda is present in the patient’s sample as compared to control subjects. Conclusion: It is therefore concluded that abnormal biochemical function of liver in alcoholism can lead to several complications, hence further research is needed to reach a definite conclusion.